Evaluation of mathematical model to characterize the performance of conventional and hybrid PV array topologies under static and dynamic shading patterns - Premkumar M.; Subramaniam U.; Sudhakar Babu T.; Elavarasan R.M.; Mihet-Popa L. (MDPI AG, 2023)
Food products; MATLAB; Photovoltaic cells; Current equation; Hybrid topologies; Multiple-peak; Partial shading; Performance analysis; Photovoltaic modules; Power out put; Series-parallel; Topology